Ginger-Enriched Honey Attenuates Antibiotic Resistant Pseudomonas aeruginosa Quorum Sensing Virulence Factors and Biofilm Formation - Wen-Jie Ng; Chin-Lu Hing; Choon-Boq Loo; Ee-Khang Hoh; Ian-Lung Loke; Kah-Yaw Ee (MDPI AG, 2023)
Quorum sensing (QS) in Pseudomonas aeruginosa plays an essential role in virulence factors, biofilm formation as well as antibiotic resistance. Approaches that target virulence factors are known to be more sustainable than antibiotics in weakening the infectivity of bacteria. Although honey has been shown to exert antipseudomonal activities, the enhancement of such activity in ginger-enriched honey is still unknown. The main objective of this study was to determine the impacts of honey and ginger-enriched honey on the QS virulence factors and biofilm formation of antibiotic resistant P. aeruginosa clinical isolates. Outcomes showed honey and/or ginger-enriched honey significantly reduced the protease activity, pyocyanin production and exotoxin A concentration of the isolates. The swarming and swimming motility together with biofilm formation in all clinical isolates were also significantly inhibited by both honey samples. Notable morphological alteration of bacterial cells was also observed using scanning electron microscopy. A principal component analysis (PCA) managed to distinguish the untreated group and treatment groups into two distinct clusters, although honey and ginger-enriched honey groups were not well differentiated. This study revealed the effectiveness of honey including ginger-enriched honey to attenuate QS virulence factors and biofilm formation of P. aeruginosa.